2001
DOI: 10.1128/iai.69.11.7190-7193.2001
|View full text |Cite
|
Sign up to set email alerts
|

Identity of Activation Molecule 3 on Superantigen-Stimulated Bovine Cells Is CD26

Abstract: Most CD8؉ T cells in cultures of bovine mononuclear cells stimulated with staphylococcal enterotoxin C1 develop an unusual phenotype characterized by expression of activation molecule 3 (ACT3). This superantigendependent phenotype may be relevant to immunopathogenesis mediated by certain microbial toxins. The size and N-terminal sequence of immunoprecipitated ACT3 indicate that ACT3 is the bovine orthologue of CD26.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Bands were visualized by silver staining (SilverQuest™ Staining Kit, Invitrogen, CA). Comparison of the band patterns revealed which band was specific for the mAb defined molecule as previously shown (Lee et al, 2001). Where possible, the specific band was further confirmed by WB with the mAb used for the IP following reducing and non-reducing SDS-PAGE conditions.…”
Section: Methodssupporting
confidence: 65%
See 1 more Smart Citation
“…Bands were visualized by silver staining (SilverQuest™ Staining Kit, Invitrogen, CA). Comparison of the band patterns revealed which band was specific for the mAb defined molecule as previously shown (Lee et al, 2001). Where possible, the specific band was further confirmed by WB with the mAb used for the IP following reducing and non-reducing SDS-PAGE conditions.…”
Section: Methodssupporting
confidence: 65%
“…A mAb designated as ACT3 clustered with mAbs submitted to the second ruminant workshop that formed workshop cluster WC10 (Naessens and Hopkins, 1996). Further studies showed the mAb ACT3 recognized CD26 (Lee et al, 2001). As mentioned below, this mAb was used in the validation of the specificity of a cluster of mAbs (ACT40) developed at a later date.…”
Section: Resultsmentioning
confidence: 99%
“…To date, these ACT molecules remain incompletely characterized, and data presented here will be beneficial as their identities become characterized (e.g., CD26 was formerly ACT3) (26). Regardless, CD4 ϩ , CD8 ϩ , and ␥␦ TCR ϩ cells from M. bovisinfected cattle exhibit an activated phenotype when restimulated with either an rESAT-6-CFP10 fusion protein or M. bovis PPD.…”
Section: Cd45romentioning
confidence: 99%
“…Additionally, there was a notable increase in the number of cells expressing CD26. The cellular upregulation of CD26, an ectoenzyme, has been associated with an activated phenotype in cattle (26). CD4 ϩ , CD8 ϩ , and ␥␦ TCR ϩ cells from M. bovis-infected cattle, but not from noninfected animals, upregulated their expression of CD26 at 6 days of culture with mycobacterial antigens (Fig.…”
Section: Pbmcs From M Bovis-infected Cattle Exhibit Robust Proliferamentioning
confidence: 99%
“…4, below). MAbs specific for CD25 and CD26 were used to monitor the activation status of ␣␤ and ␥␦ T cells and other cells in the cultures (23,40). An additional MAb was used to monitor the upregulation of a molecule, ACT2, uniquely expressed on activated ␥␦ T cells ( Table 2; Fig.…”
Section: Wc1mentioning
confidence: 99%